2016
DOI: 10.3389/fendo.2016.00067
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Interplay between Bone Marrow Adipose Tissue and Multiple Myeloma cells

Abstract: In the year 2000, Hanahan and Weinberg (1) defined the six Hallmarks of Cancer as: self-sufficiency in growth signals, evasion of apoptosis, insensitivity to antigrowth mechanisms, tissue invasion and metastasis, limitless replicative potential, and sustained angiogenesis. Eleven years later, two new Hallmarks were added to the list (avoiding immune destruction and reprograming energy metabolism) and two new tumor characteristics (tumor-promoting inflammation and genome instability and mutation) (2). In multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 186 publications
0
73
0
2
Order By: Relevance
“…Decreasing MAT may result in stronger bones, while strengthening bones may result in decreased MAT through feedback systems that may prove to be beneficial when targeting the microenvironment for MM and other tumor cells within the BM. More on the specifics of MAT-MM interactions can be found in our recent publication on this topic [84]. …”
Section: Myeloma Interaction With Bm Elementsmentioning
confidence: 99%
“…Decreasing MAT may result in stronger bones, while strengthening bones may result in decreased MAT through feedback systems that may prove to be beneficial when targeting the microenvironment for MM and other tumor cells within the BM. More on the specifics of MAT-MM interactions can be found in our recent publication on this topic [84]. …”
Section: Myeloma Interaction With Bm Elementsmentioning
confidence: 99%
“…The role of the central nervous system in bone metabolism and the specific role of adiponectin in skeletal metabolism are addressed in this issue. Moving towards the skeletal microenvironment, metabolically active marrow adipose tissue has the potential to influence and control local processes [18] and may also contribute to the development of disease such as myeloma [19]. In this issue, McDonald et al provide a comprehensive review on how cells in the bone microenvironment including adipocytes contribute to the origin of multiple myeloma, and the subsequent disease progression and drug resistance.…”
mentioning
confidence: 99%
“…A handful of studies in myeloma have found that MAT produces factors that support myeloma disease progression, although certain adipokines, such as adiponectin [16], have been found to inhibit myeloma, confounding the roles of MAT in myeloma [17,18]. Cell-derived factors (molecules, lipids, small metabolites, or microRNAs) may be free or embedded in exosomes or other microvesicles and transferred between BMAs and myeloma cells as one method of communication [19].…”
Section: Mat Adipokines Lipids and Cell-cell Contact Supports Camentioning
confidence: 99%